Topics for Discussion in Oral Communication Courses: A Proposal Based on the United Nations’ 2030 Agenda for Sustainable Development and the 2023 Estado de la Nación Report - Angulo - Jiménez, Henry (UNIVERSIDAD ESTATAL A DISTANCIA, 2024)
This paper documents the process whereby a proposal of topics for discussion in the oral communication courses of the Bachelor’s degree in English of a Costa Rican public university was developed. More specifically, the manuscript describes how topics of national and international relevance were (a) inductively identified in the United Nations’ 2030 Agenda for Sustainable Development, (b) further specified through both inductive and deductive thematic analysis of relevant segments and sections of the 2023 Estado de la Nación report, and (c) distributed across the six oral communication courses of the Bachelor’s degree in English at the University of the Central Valley (UCV), with the least feasible disruption to existing syllabi and maximum possible overlap with other courses within the same block in the study program. The process resulted in the identification of 52 topics of international and national relevance (e.g., climate change and actions to combat it), the addition of six topics from the 2023 Estado de la Nación Report (e.g., threats to freedom of expression), the categorization of said topics under six macro-topics (e.g., vulnerable groups: issues and empowerment), and the distribution of these six macro-topics across the six oral communication courses of the BA in English at UCV.